Implementasi Program Literasi dalam Menumbuhkan Minat Baca dan Prestasi Akademik Siswa - Masruroh, Laily; Ilahiyah, Iva Inayatul; Khusnul, Mokhamad (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
The low reading interest among students remains a challenge in education as it directly affects their academic achievement. To address this issue, MTs Baiturrohim Blimbing Jombang has implemented a literacy program integrated into the learning process. This study aims to describe the implementation of the literacy program, its influence on students’ reading interest and academic achievement, as well as the supporting and inhibiting factors in its execution. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation involving the school principal, literacy program teachers, and students. The findings reveal that the literacy program is carried out through structured reading activities, the provision of reading corners in each classroom, library facilities, the use of educational technology, and the integration of literacy into various subjects. The program has successfully fostered reading interest, enhanced learning motivation, and positively impacted students’ cognitive, affective, and psychomotor aspects. Supporting factors include the availability of learning facilities, technology, and internet access, while inhibiting factors involve students’ low reading ability, limited book collections, inadequate technological resources, uneven internet access, and insufficient supervision of digital device usage. This study recommends improving reading skills training, increasing book and technology resources, expanding internet coverage, and strengthening the supervision of technology use to ensure the literacy program’s optimal and sustainable implementation.